Estimates of genomic inbreeding and identification of candidate regions that differ between Chinese indigenous sheep breeds. - Liu J; Shi L; Li Y; Chen L; Garrick D; Wang L; Zhao F (BioMed Central Ltd, 2021)
BACKGROUND: A run of homozygosity (ROH) is a consecutive tract of homozygous genotypes in an individual that indicates it has inherited the same ancestral haplotype from both parents. Genomic inbreeding can be quantified based on ROH. Genomic regions enriched with ROH may be indicative of selection sweeps and are known as ROH islands. We carried out ROH analyses in five Chinese indigenous sheep breeds; Altay sheep (n = 50 individuals), Large-tailed Han sheep (n = 50), Hulun Buir sheep (n = 150), Short-tailed grassland sheep (n = 150), and Tibetan sheep (n = 50), using genotypes from an Ovine Infinium HD SNP BeadChip. RESULTS: A total of 18,288 ROH were identified. The average number of ROH per individual across the five sheep breeds ranged from 39 (Hulun Buir sheep) to 78 (Large-tailed Han sheep) and the average length of ROH ranged from 0.929 Mb (Hulun Buir sheep) to 2.544 Mb (Large-tailed Han sheep). The effective population size (Ne) of Altay sheep, Large-tailed Han sheep, Hulun Buir sheep, Short-tailed grassland sheep and Tibetan sheep were estimated to be 81, 78, 253, 238 and 70 five generations ago. The highest ROH-based inbreeding estimate (FROH) was 0.0808 in Large-tailed Han sheep, whereas the lowest FROH was 0.0148 in Hulun Buir sheep. Furthermore, the highest proportion of long ROH fragments (> 5 Mb) was observed in the Large-tailed Han sheep breed which indicated recent inbreeding. In total, 49 ROH islands (the top 0.1% of the SNPs most commonly observed in ROH) were identified in the five sheep breeds. Three ROH islands were common to all the five sheep breeds, and were located on OAR2: 12.2-12.3 Mb, OAR12: 78.4-79.1 Mb and OAR13: 53.0-53.6 Mb. Three breed-specific ROH islands were observed in Altay sheep (OAR15: 3.4-3.8 Mb), Large-tailed Han sheep (ORA17: 53.5-53.8 Mb) and Tibetan sheep (ORA5:19.8-20.2 Mb). Collectively, the ROH islands harbored 78 unique genes, including 19 genes that have been documented as having associations with tail types, adaptation, growth, body size, reproduction or immune response. CONCLUSION: Different ROH patterns were observed in five Chinese indigenous sheep breeds, which reflected their different population histories. Large-tailed Han sheep had the highest genomic inbreeding coefficients and the highest proportion of long ROH fragments indicating recent inbreeding. Candidate genes in ROH islands could be used to illustrate the genetic characteristics of these five sheep breeds. Our findings contribute to the understanding of genetic diversity and population demography, and help design and implement breeding and conservation strategies for Chinese sheep.
Keywords: Candidate genes; Genomic inbreeding coefficient; ROH islands; Runs of homozygosity; Sheep